2022
DOI: 10.1097/mpg.0000000000003636
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of Paper and Electronic-Based Patient Reported Outcome Measures for Children: A Systematic Review

Abstract: Patient-reported outcome measures (PROMs) exist for a variety of chronic gastrointestinal disorders in children. The availability of electronic (e-)formats of PROMs enhance the accessibility of these tools. The International Society for Pharmacoeconomic and Outcomes Research (ISPOR) defines measurement equivalence (ME) as “comparability of the psychometric properties of data” obtained from the administration of original and adapted versions of PROMs. Consideration of proxy PROM versions is unique to pediatrics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…3,4 T A B L E 1 Mean scores and agreement between tablet and paper-based versions of the PeLTQL total and subdomain scores : ICC, intraclass correlation coefficient; PeLTQL, Pediatric Liver Transplant Quality of Life questionnaire.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 T A B L E 1 Mean scores and agreement between tablet and paper-based versions of the PeLTQL total and subdomain scores : ICC, intraclass correlation coefficient; PeLTQL, Pediatric Liver Transplant Quality of Life questionnaire.…”
mentioning
confidence: 99%
“…[3] Despite these recommendations, in a recent systematic review evaluating ME of pediatric PROMs, fewer than a third of included studies reported ME data on both self and proxy-reported versions. [4] Children who have undergone liver transplantation (LT) transition through multiple phases of the medical journey, ultimately to a chronic management phase aimed at sustaining long-term allograft function, minimizing the sequelae of long-term immune suppression, and maximizing other aspects of health and wellness. PROM utilization would thereby provide key insights on patient perspectives to complement life-long medical surveillance.…”
mentioning
confidence: 99%
See 1 more Smart Citation